BIOLOGICAL CONTROL OF LEAF SPOT DISEASE (Phyllosticta zingiberi) ON RED GINGER (Zingiber officinale Rosc.) USING BIOCONTROL AGENTS - Martha Adiwaty Sihaloho; Hapsoh; Hasanuddin (Prodi Agroteknologi Fakultas Agro Teknologi Universitas Prima Indonesia, 2026)
Leaf spot disease is one of the major constraints in red ginger (Zingiber officinale Rosc.) cultivation, causing significant economic losses to farmers and reducing national export value. The disease is suspected to be seed-borne, as the pathogen can survive in infected planting materials. This study aimed to evaluate the effectiveness of the biocontrol fungi Trichoderma koningii, T. harzianum, Gliocladium spp., and G. virens in suppressing Phyllosticta zingiberi, the causal agent of leaf spot disease.. Additionally, the study assessed different application methods of biocontrol agents in controlling the disease. The study was conducted at the Experimental Field of the Faculty of Agriculture, Universitas Amir Hamzah, Medan Estate Village, Percut Sei Tuan District, Deli Serdang Regency, at an altitude of approximately 25 m above sea level, from January to August 2010. The study consisted of two main stages: (1) identification of the causal pathogen of leaf spot disease in red ginger, and (2) in vitro antagonistic testing of biocontrol agents against P. zingiberi. The results showed that the application of antifungal suspension of Gliocladium virens on leaves was relatively more effective in inhibiting the growth of P. zingiberi compared to other tested biocontrol agents